Olho por olho, dente por dente em 140 caracteres: comportamento de retaliação por usuários de serviço público no Twitter. - Pinheiro, Pablo Ramon de Lima (2012)
The daily life has been marked by interactions in cyberspace, it is noteworthy in this context the use of social media on the Internet, which have enabled individuals to an unprecedented level of connection. This network of individuals makes possible the dissemination of ideas to people in a very short time period. For organizations this aspect can be positive, and negative as well, since a retaliation message may take unwanted proportion in the network. In this regard, many government agencies began to mobilize efforts to monitor users' interactions on social media such as Twitter and Facebook. This study was aimed to categorize the retaliation behavior from users of public services on the micro blogging tool known as Twitter following the profiles linked to the city of João Pessoa municipal administration. The equity theory proposed by Adams (1965) was used on the research. A qualitative approach was adopted. The study used a corpus composed of retaliation messages collected directly from Twitter and stored in a database. To perform the analysis, the researcher adopted the content analysis technique, using a priori categories as defined in the work of Huefner and Hunt (2000) and Albuquerque, Pereira, Bellini (2011), and the categories a posteriori that emerged throughout the analysis. The strategy for classifying posts was divided on category, retaliation motivation and fairness perception. The analysis resulted in seven categories of retaliation and six motivational aspects of behavior, which led to the understanding of conceptual differences between products and services consumption from the private sector and public services. The differences are reflected regarding the retaliation types chosen. The research detected that the behavior of retaliation can provide organizations with information relevant to the establishment of e-government strategies and social media marketing.